TGF-β1 Downregulates the Expression of CX3CR1 by Inducing miR-27a-5p in Primary Human NK Cells - Regis, Stefano; Caliendo, Fabio; Dondero, Alessandra; Casu, Beatrice; Romano, Filomena; Loiacono, Fabrizio; Moretta, Alessandro; Bottino, Cristina; Castriconi, Roberta (Frontiers in Immunology, 2017)
Activity of human natural killer (NK) cells against cancer cells is deeply suppressed by TGF-β1, an immunomodulatory cytokine that is released and activated in the tumor microenvironment. Moreover, our previous data showed that TGF-β1 modifies the chemokine receptor repertoire of NK cells. In particular, it decreases the expression of CX3CR1 that drives these effectors toward peripheral tissues, including tumor sites. To identify possible mechanisms mediating chemokine receptors modulation, we analyzed the microRNA profile of TGF-β1-treated primary NK cells. The analysis pointed out miR-27a-5p as a possible modulator of CX3CR1. We demonstrated the functional interaction of miR-27a-5p with the 3′ untranslated region (3′UTR) of CX3CR1 mRNA by two different experimental approaches: by the use of a luciferase assay based on a reporter construct containing the CX3CR1 3′UTR and by transfection of primary NK cells with a miR-27a-5p inhibitor. We also showed that the TGF-β1-mediated increase of miR-27a-5p expression is a consequence of miR-23a-27a-24-2 cluster induction. Moreover, we demonstrated that miR-27a-5p downregulates the surface expression of CX3CR1. Finally, we showed that neuroblastoma cells induced in resting NK cells a downregulation of the CX3CR1 expression that was paralleled by a significant increase of miR-27a-5p expression. Therefore, the present study highlights miR-27a-5p as a pivotal TGF-β1-induced regulator of CX3CR1 expression.